Construction of Plasmonic Metal@Semiconductor Core–Shell Photocatalysts: From Epitaxial to Nonepitaxial Strategies. Issue 9 (5th June 2022) - Wan, Xiaodong; Liu, Jia; Zhang, Jiatao
Abstract : In recent decade, plasmonic metal@semiconductor core–shell nanostructures have sparked tremendous research interest toward development of advanced photocatalysts. This is because such materials facilitate to harness the localized surface plasmon resonant absorption of plasmonic metal nanoparticles tunable across the entire ultraviolet–visible–near infrared (UV–vis–NIR) region, for improving the photocatalytic efficiency of surrounding semiconductors via multiple energy and charge carrier flow channels. Herein, the recent synthetic progresses achieved in wet chemical preparation of plasmonic metal@semiconductor core–shell photocatalysts are outlined. Tentatively, the reported synthetic approaches are classified into three major groups including the epitaxial seeded growth, the kinetically overdriven nonepitaxial seeded growth, and the cation exchange‐facilitated (CEf) nonepitaxial growth dictated by chemical thermodynamics. Special focuses are laid on elucidating the fundamental correlation of the synthetic mechanism with the crystallographic and physical properties of the resultant nanostructures that strongly dominate the synergistic coupling efficiency between plasmonic metal and semiconductor. Of these, the promise of CEf nonepitaxy in curbing the formation of interfacial defect states and promoting extraction of plasmonic hot carriers from the large lattice‐mismatched hybrid photocatalysts is detailedly elaborated. A comprehensive understanding in this scope is of significance for rationally architecting the plasmonic metal@semiconductor core–shell nanostructures toward disclosing fascinating horizons in photocatalytic solar‐to‐fuel conversion. Abstract : Herein, the recent synthetic progresses achieved in wet‐chemical preparation of plasmonic metal@semiconductor core–shell photocatalysts are outlined. Special focuses on elucidating the aspects of thermodynamics and kinetics relevant to synthetic mechanism, and their impacts on the crystallographic and optoelectronic properties of resultant materials that dominate the synergistic coupling efficiency between plasmonic metal and semiconductor in solar‐to‐fuel conversion process are laid.